Social divisions in school participation and attainment in India: 1983 - 2004 - Niaz Asadullah; Uma Kambhampati; Florencia López Bóo (Institute for the Study of Labor (IZA), 2012)
This study documents the size and nature of Hindu-Muslim and boy-girl gaps in children's school participation and attainments in India. Individual-level data from two successive rounds of the National Sample Survey suggest that considerable progress has been made in decreasing the Hindu-Muslim gap. Nonetheless, the gap remains sizable even after controlling for numerous socio-economic and parental covariates, and the Muslim educational disadvantage in India today is greater than that experienced by girls and Scheduled Caste Hindu children. A gender gap still appears within as well as between communities, though it is smaller within Muslim communities. While differences in gender and other demographic and socio-economic covariates have recently become more important in explaining the Hindu-Muslim gap, those differences altogether explain only 25 percent to 45 percent of the observed schooling gap.
urn:nbn:de:101:1-2012042311263
Keywords: I21; O15; 330; gender inequality; India; religion; social disparity; Schulbesuch; Bildungsniveau; Religion; Ethnische Diskriminierung; Geschlechterdiskriminierung; Indien